The N-terminus of Paenibacillus larvae C3larvinA modulates catalytic efficiency. Issue 1 (29th January 2021) - Turner, Madison; Heney, Kayla A.; Merrill, A. Rod
Abstract: C3larvinA was recently described as a mono-ADP-ribosyltransferase (mART) toxin from the enterobacterial repetitive intergenic consensus (ERIC) III genotype of the agricultural pathogen, Paenibacillus larvae . It was shown to be the full-length, functional version of the previously described C3larvintrunc toxin, due to a 33-residue extension of the N-terminus of the protein. In the present study, a series of deletions and substitutions were made to the N-terminus of C3larvinA to assess the contribution of the α1 -helix to toxin structure and function. Catalytic characterization of these variants identified Asp 23 and Ala 31 residues as supportive to enzymatic function. A third residue, Lys 36, was also found to contribute to the catalytic activity of the enzyme. Analysis of the C3larvinA homology model revealed that these three residues were participating in a series of interactions to properly orient both the Q-X-E and S-T-S motifs. Ala 31 and Lys 36 were found to associate with a structural network of residues previously identified in silico, whereas Asp 23 forms novel interactions not previously described. At last, the membrane translocation activity into host target cells of each variant was assessed, highlighting a possible relationship between protein dipole and target cell entry.